Interpretation of Literature Piracy in Tere Liye's Novel Title "Selamat Tinggal" A Study of Literature Sociology - Miranti Miranti (International Journal of Science and Applied Science: Conference Series, 2022)
Sociology of literature is like an imitation, to see the real situation and social phenomena that occur. in the imaginative world, there are always events in the real world that then become part of the storytelling. Literature then blends and blends between real events and fictional events. With existing innovations, hidden realities can be brought back. The object of this research is a novel entitled "Selamat Tinggal”. This novel tells about Sintong, a student who works as a keeper of a pirated bookstore: "Berkah". Sintong is a graduate student from the faculty of literature. Ideally, he does not agree with his work as a mediator for pirated books to be sold. But conditionally, only selling pirated books, Sintong can continue her studies. Understandably, he is an overseas child who has not received any money from his parents. Even guarding a bootleg shop next to the station, because the owner of the blessing shop is his own Paklik. This research method is a qualitative research method. According to Moleong, for this qualitative research to understand the phenomena of what is experienced by the research subject, for example, perceptual behavior, motivation, action and others holistically, and by way of description in the form of words and language, in a special context that is natural and by utilizing various natural methods. With this the data presented in this study are in the form of words, phrases, sentences, and the context of the story in the novel. This qualitative descriptive research is descriptive and analyzes the problems contained in the novel objectively. This study is to compare the fictional events in the novel with the reality that occurs in the real world. One example that is closest to us is students who prefer to buy pirated books rather than original books. Of course, the advantage of pirated books is that they are much cheaper than original books. The student's mediocre economic situation supports this. Sintong even when selling pirated books, has a lot of subscribers who are among students. The name of the pirated bookstore is "Berkah". This becomes a kind of satire by the author towards the world of piracy. The word blessing has a positive connotation, meaning "a lot of good". This is because the market share of pirated books is the weak economy. The goal is that ordinary people can get a lot of good from reading pirated books. Of course, the hijacked books are the “best sellers”, which have a lot of good in them. But this is actually satire. Sintong himself realized that "there is no blessing in stealing". Sintong is well aware that book piracy is a crime that is prohibited by law. But until now, the law that was at the beginning of the book has only been a decoration because no one has ever been prosecuted for pirating a book. Sintong himself is a writer. He wrote his thoughts in the mass media. He knows very well that pirated books are stealing the writer's fortune. The writer does not get a penny of money from the results of his hard work writing. The ones who get a lot of material benefits from pirated books are the producers. He simply reproduced what was already there, without ever paying for writers, cover designs, editors, lay outs, distributors and others. Just simply copy what is already there, then sell it for less than half the price of the original book. Of course that was enough profit.